Deviations from environmental baseline: Detection of subsea CO2 release in the water column from real-time measurements at a potential offshore Carbon Dioxide Storage site. (July 2021) - Martínez-Cabanas, María; Esposito, Mario; Gros, Jonas; Linke, Peter; Schmidt, Mark; Triest, Jack; Achterberg, Eric P.
Highlights: Real-time monitoring of CO2 release. Measurements of water column pH and pCO2 via towed Video-CTD system. Assessment of towed sensors capacity to detect potential CO2 leakage in the water column. Estimation of thresholds for the detection of anomalous pCO2 . Abstract: Within the framework of the STEMM-CCS project, a controlled CO2 release experiment was conducted under real-life conditions in the Goldeneye complex area, a depleted gas field located in the UK sector of the North Sea. Here, the viability of water column monitoring for the detection of the injected CO2 is evaluated. Real-time pH and pCO2 measurements were taken in the water column during the CO2 release experiment. Monitoring was carried out throughout the full water column, from the near-seafloor to the sea surface, in order to assess the spatial extent of the CO2 release. The dispersion of the CO2 plume was strongly influenced by tidal circulation in the area. The strongest signals were detected within 8 m of the bubble stream during low tide. The lowest pH and highest pCO2 values were 7.965 and 942.1 µatm, respectively, corresponding to variations of 16.4% [ H + ] and 125.6% from baseline values. The pCO2 baseline dynamics of Goldeneye area were assessed by the evaluation of the natural pCO2 -O2 covariance. The estimation of seasonal thresholds for anomalous pCO2 (pCO2 :O2 ratio May = 1.63 ± 0.04) allowed us to assess with confidence the non-biological origin of the detected CO2 during the release experiment.